Analisis Manajemen Risiko dalam Upaya Meningkatkan Keberlangsungan Usaha di Tengah Ketidakpastian Ekonomi - Merlina Gustin; Ika Ismatul Hawa; Novita Safitri; Ernina Elisa; Rinda Asytuti (Jurnal Kewirausahaan dan Bisnis, 2026)
This study aims to examine the role of risk management in increasing business desirability amidst an economic downturn. Economic uncertainty characterized by inflation, price fluctuations, and changes in market demand give rise to various risks that can disrupt business stability, particularly in the UMKM sector. This study uses a qualitative approach with a literature review method through analysis of various relevant scientific sources over the past five years. The results show that the main risks faced by businesses include financial, operational, market, and strategic risks, with financial and market risks being the most significant factors. The implementation of effective risk management has been proven to help business actors systematically identify, analyze, and mitigate risks, thereby increasing business resilience. In addition, adaptation strategies such as product innovation, cost efficiency, and the use of digital technology are crucial to address changes in the business environment. Therefore, the integration of risk management and appropriate adaptation strategies can improve business sustainability in a sustainable economic environment.